Descriptions of Philodinavus koreanus n. sp. and two new species of Philodina (Rotifera, Bdelloidea) from Korea - Song, Min Ok; Lee, Chang-Ho (Zootaxa, 2022)
The bdelloid rotifers collected from terrestrial habitats such as leaf litter, mosses and tree barks were studied and three new species were identified: Philodina haejooni n. sp., P. hongcheonensis n. sp. and Philodinavus koreanus n. sp. Philodina haejooni n. sp. is easily distinguished from its congeners by the leaf margin-shaped longitudinal ridges on trunk. The most significant diagnostic characteristic of Philodina hongcheonensis n. sp. is the four dorsal hemispherical processes on anal pseudosegment. Philodinavus koreanus n. sp. is the thirdly described species for the genus. The detailed morphologies of ciliated buccal fields, cheeks and spurs make Philodinavus koreanus n. sp. distinguishable from its two congeners. Here these three new species are described and illustrated. The partial sequences of mitochondrial cytochrome c oxidase subunit 1 gene (mtCOX1) for three new species are presented as well.